Al2o3p / al-fe composite material and preparation method thereof

CN117862491BActive Publication Date: 2026-10-30INNER MONGOLIA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310695342.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2026-10-30
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

为了制备得到理想的Al-Fe复合材料,通常向Al-Fe复合材料中加入稀土等其它元素,但这就导致复合材料的生产成分增加

Benefits of technology

[0019]本发明利用Al-Fe2O3之间的原位反应制备Al2O3P/Al-Fe复合材料,并通过调整和控制Fe2O3的含量、加热方式,以及原位反应温度和保温时间使得Al2O3P/Al-Fe复合材料中生成特定形状的氧化铝颗粒和Al3Fe相,二者共同作用使得Al2O3P/Al-Fe复合材料具有较高的硬度和较好的耐磨性;本发明的制备方法不需要通入惰性气体保护就可以避免铝粉和氧化铁粉原位反应时铝粉的氧化,制备工艺简单、不需要额外添加其它元素就能制备得到较好性能的Al2O3P/Al-Fe复合材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117862491B_ABST
    Figure CN117862491B_ABST
Patent Text Reader

Abstract

The application discloses Al2O 3P / Al-Fe composite material, the composite material has alumina particles and Al3Fe phase; the existing form of the alumina particles is one or two or more than two of agglomerates, rods, near-spheres and irregular shapes; the existing form of the Al3Fe phase is one or two or more than two of discontinuous particles, needles, rods or blocks; the preparation method comprises the following steps: (1) drying nano-magnetic iron oxide powder and cooling to room temperature immediately, then fully mixing with aluminum powder to obtain mixed raw material powder; (2) pressing the mixed raw material powder to obtain a cylindrical preform; (3) sintering the cylindrical preform in a resistance furnace. The preparation method can avoid oxidation of aluminum powder during in-situ reaction of aluminum powder and iron oxide powder without passing inert gas protection, and the preparation process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of Al-Fe composite materials technology. Specifically, it relates to an Al2O3 composite material. 3P Preparation method of Al-Fe composite material. Background Technology

[0002] Al2O 3P Al-Fe composites possess excellent properties such as light weight, high specific strength and modulus, wear resistance, and high temperature resistance, making them promising for applications in aerospace, electronics, and automotive manufacturing industries. The increased amount of hard reinforcing phases (Al₂O₃ particles and Al₃Fe intermetallic compounds) in Al-based composites leads to higher hardness and wear resistance. However, the morphology, quantity, and distribution of the reinforcing phases significantly influence the composite's performance. These properties are affected by a combination of factors, including the raw material state, processing method, and process parameters. To obtain ideal Al-Fe composites, rare earth elements and other elements are often added, which increases the required composition of the composite material. Summary of the Invention

[0003] Therefore, the technical problem to be solved by the present invention is to provide an Al2O that has a simple preparation process and does not require the addition of other elements. 3P / Al-Fe composite materials and their preparation methods.

[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0005] A type of Al2O 3P / Al-Fe composite material, the composite material contains alumina particles and Al3Fe phase; the alumina particles exist in the form of alumina particle aggregates, rods, near-spherical and irregular shapes, or a mixture of two or more of them; the Al3Fe phase exists in the form of discontinuous granular, needle-like, rod-like or blocky shapes, or a mixture of two or more of them.

[0006] The above Al2O 3P The preparation method of Al-Fe composite material includes the following steps:

[0007] Step (1): After drying the nano-magnetic iron oxide powder and cooling it to room temperature, immediately mix it thoroughly with aluminum powder to obtain a mixed raw material powder;

[0008] Step (2): Press the mixed raw material powder into a cylindrical preform.

[0009] Step (3): Place the cylindrical preform into a resistance furnace for sintering. After sintering, Al2O3 is obtained.3P / Al-Fe composite material.

[0010] The above Al2O 3P The preparation method of Al-Fe composite material, in step (1), the particle size of aluminum powder is 30-80 μm and the purity is greater than or equal to 99.0 wt.%; the particle size of nano magnetic iron oxide powder is 5-40 nm and the purity is greater than or equal to 98.0 wt.%; the mass fraction of nano magnetic iron oxide powder in the mixed raw material powder is 2-20 wt.%.

[0011] The above Al2O 3P The preparation method of Al-Fe composite material, in step (1), the drying temperature of nano-magnetic iron oxide powder is 150-300℃ and the drying time is 1.5-2.5h. Under this drying temperature and drying time, the moisture in the iron oxide powder can be effectively removed and the iron oxide powder will not sinter. Thus, the moisture adsorbed on the surface of nano-magnetic iron oxide powder can be effectively removed. Otherwise, the nano-magnetic iron oxide powder will agglomerate during the mixing process, affecting the uniformity of the mixed raw materials. The mixing time with aluminum powder after drying is 20-35min.

[0012] The above Al2O 3P The preparation method of Al-Fe composite material, in step (1), the drying temperature of nano magnetic iron oxide powder is 180℃ and the drying time is 2h; the mixing time with aluminum powder after drying is 30min.

[0013] The above Al2O 3P In the preparation method of Al-Fe composite material, in step (2), the material is pressed at room temperature with a pressure of 75-85 kN and a holding time of 160-200 s. If the pressure is too low, the density of the pressed block will be poor; if the pressure is too high, the residual stress in the pressed block will be large.

[0014] The above Al2O 3P In the preparation method of Al-Fe composite material, in step (2), the pressure during pressing is 80 kN and the holding time is 180 s; the dimensions of the cylindrical preform are... If the cylindrical precast blocks are too large, they will easily deform during the reaction process; if they are too small, they will release less heat during the reaction process, requiring higher temperatures or longer holding times to maintain the reaction.

[0015] The above Al2O 3P In the preparation method of Al-Fe composite material, in step (3), the heating method during sintering is to heat the furnace with the furnace or to put it into the furnace when the temperature reaches a certain level.

[0016] The above Al2O 3PIn the preparation method of Al-Fe composite material, in step (3), when heating with the furnace: the cylindrical preform is placed in the resistance furnace and heated to 1200℃ at a rate of 5℃ / min, and kept at the temperature for 10min or 1h.

[0017] The above Al2O 3P In the preparation method of Al-Fe composite material, in step (3), when the temperature is reached for the furnace: first raise the temperature of the resistance furnace to 1100-1200℃, then put the cylindrical preform into the resistance furnace and keep it warm for 10 minutes or 1 hour.

[0018] The technical solution of the present invention achieves the following beneficial technical effects:

[0019] This invention utilizes the in-situ reaction between Al and Fe2O3 to prepare Al2O3. 3P Al-Fe composite materials were developed, and the content of Fe2O3, heating method, in-situ reaction temperature, and holding time were adjusted and controlled to optimize the Al2O3 content. 3P In Al-Fe composites, alumina particles of specific shapes and the Al3Fe phase are formed, and their combined action leads to the formation of Al2O3 phase. 3P Al-Fe composite materials exhibit high hardness and good wear resistance. The preparation method of this invention avoids the oxidation of aluminum powder during the in-situ reaction of aluminum powder and iron oxide powder without the need for inert gas protection. The preparation process is simple and does not require the addition of other elements to obtain Al2O3 with good performance. 3P / Al-Fe composite material. Attached Figure Description

[0020] Figure 1 Al2O in the embodiments of the present invention 3P Schematic diagram of the preparation process of Al-Fe composite materials;

[0021] Figures 2a to 2d BSE diagrams of compressed blocks with different Fe2O3 contents in the embodiments of the present invention: (a) Al-2wt.%Fe2O3, (b) Al-3wt.%Fe2O3, (c) Al-4wt.%Fe2O3, (d) Al-20wt.%Fe2O3;

[0022] Figures 3a to 3h In-situ Al2O prepared at different temperatures in the embodiments of the present invention 3POM diagram of Al2O3 particle dispersion in Al-Fe composite material: At 1100℃, the mass percentage of Fe is (a) 1.4wt.%, (c) 2.1wt.%, (e) 2.8wt.% and (g) 14wt.%; At 1200℃, the mass percentage of Fe is (b) 1.4wt.%, (d) 2.1wt.%, (f) 2.8wt.% and (h) 14wt.%.

[0023] Figures 4a to 4h In-situ Al2O prepared at different temperatures in the embodiments of the present invention 3P SEM images of dispersed Al2O3 particles in Al-Fe composites: At 1100℃, the mass percentage of Fe was (a) 1.4 wt.%, (c) 2.1 wt.%, (e) 2.8 wt.%, and (g) 14 wt.%; at 1200℃, the mass percentage of Fe was (b) 1.4 wt.%, (d) 2.1 wt.%, (f) 2.8 wt.%, and (h) 14 wt.%.

[0024] Figures 5a to 5f In-situ Al2O prepared at different temperatures in the embodiments of the present invention 3P SEM images of Al2O3 particle agglomerates in Al-Fe composites: At 1100℃, the mass percentage of Fe is (a) 1.4 wt.%, (c) 2.1 wt.% and (e) 2.8 wt.%; at 1200℃, the mass percentage of Fe is (b) 1.4 wt.%, (d) 2.1 wt.% and (f) 2.8 wt.%.

[0025] Figures 6a to 6h In-situ Al2O prepared at different temperatures in the embodiments of the present invention 3P The influence of Al3Fe phase distribution on the BSE diagram in Al-Fe composites: At 1100℃, the mass percentage of Fe is (a) 1.4 wt.%, (c) 2.1 wt.%, (e) 2.8 wt.%, and (g) 14 wt.%; at 1200℃, the mass percentage of Fe is (b) 1.4 wt.%, (d) 2.1 wt.%, (f) 2.8 wt.%, and (h) 14 wt.%.

[0026] Figures 7a to 7d In-situ Al2O in this embodiment of the invention 3P Morphology of discontinuous Al3Fe phase in Al-Fe composite material: (a) discontinuous needle-like, (b) discontinuous rod-like, (c) discontinuous blocky when Fe content is low, (d) discontinuous blocky when Fe content is high;

[0027] Figures 8a to 8hIn-situ Al2O prepared at different temperatures in the embodiments of the present invention 3P OM diagram of Al2O3 particle dispersibility in Al-Fe composite material: At 1100℃, the mass percentage of Fe is (a) 1.4wt.%, (c) 2.1wt.%, (e) 2.8wt.% and (g) 14wt.%; At 1200℃, the mass percentage of Fe is (b) 1.4wt.%, (d) 2.1wt.%, (f) 2.8wt.% and (h) 14wt.%.

[0028] Figures 9a to 9h In-situ Al2O prepared at different temperatures in the embodiments of the present invention 3P SEM images of dispersed Al2O3 particles in Al-Fe composites: At 1100℃, the mass percentage of Fe was (a) 1.4 wt.%, (c) 2.1 wt.%, (e) 2.8 wt.%, and (g) 14 wt.%; at 1200℃, the mass percentage of Fe was (b) 1.4 wt.%, (d) 2.1 wt.%, (f) 2.8 wt.%, and (h) 14 wt.%.

[0029] Figures 10a to 10h In-situ Al2O prepared at different temperatures in the embodiments of the present invention 3P BSE diagram of Al3Fe phase in Al-Fe composite material: At 1100℃, the mass percentage of Fe is (a) 1.4 wt.%, (c) 2.1 wt.%, (e) 2.8 wt.% and (g) 14 wt.%; At 1200℃, the mass percentage of Fe is (b) 1.4 wt.%, (d) 2.1 wt.%, (f) 2.8 wt.% and (h) 14 wt.%.

[0030] Figures 11a to 11h The following diagram illustrates the effect of heating method on the dispersibility of Al2O3 particles in the composite material in this embodiment of the invention: With furnace heating at 5℃ / min, the mass percentage of Fe was (a) 1.4 wt.%, (c) 2.1 wt.%, (e) 2.8 wt.%, and (g) 14 wt.%; when directly placed in the furnace, the mass percentage of Fe was (b) 1.4 wt.%, (d) 2.1 wt.%, (f) 2.8 wt.%, and (h) 14 wt.%.

[0031] Figures 12a to 12h The heating method for in-situ Al2O in this embodiment of the invention 3PThe effect of dispersed Al2O3 particles in Al-Fe composites: SEM images: When the furnace temperature is increased at 5℃ / min, the mass percentage of Fe is (a) 1.4wt.%, (c) 2.1wt.%, (e) 2.8wt.% and (g) 14wt.%, respectively; when directly placed in the furnace, the mass percentage of Fe is (b) 1.4wt.%, (d) 2.1wt.%, (f) 2.8wt.% and (h) 14wt.%, respectively.

[0032] Figures 13a to 13h The heating method for in-situ Al2O in this embodiment of the invention 3P The effect of Al3Fe phase on Al-Fe composites (BSE diagram): With furnace heating at 5℃ / min, the mass percentage of Fe was (a) 1.4wt.%, (c) 2.1wt.%, (e) 2.8wt.%, and (g) 14wt.%; when directly placed in the furnace, the mass percentage of Fe was (b) 1.4wt.%, (d) 2.1wt.%, (f) 2.8wt.%, and (h) 14wt.%.

[0033] Figure 14 In this embodiment of the invention, in-situ Al2O2 prepared at different temperatures after being kept at a temperature of 10 min was obtained. 3P Hardness bar chart of Al-Fe composite material;

[0034] Figure 15 In this embodiment of the invention, in-situ Al2O2 prepared at different temperatures after being kept at a temperature of 1 hour was obtained. 3P Hardness bar chart of Al-Fe composite material;

[0035] Figure 16 In this embodiment of the invention, Al2O is prepared by in-situ reaction at 1200℃ using a heating method. 3P Bar chart showing the effect of hardness on Al-Fe composite materials;

[0036] Figure 17 In this embodiment of the invention, in-situ Al2O2 prepared at different temperatures after being kept at a temperature of 10 min was obtained. 3P A bar chart of wear amount of Al-Fe composite material;

[0037] Figures 18a to 18h SEM images of the wear sample surface directly placed in a 1200℃ furnace and held for 10 min in this embodiment of the invention: (a) and (b) are Al2O3 and Al2O3, respectively. 3P / Al-1.4wt.%Fe, (c) and (d) are Al2O 3P / Al-2.1wt.%Fe; (e) and (f) are Al2O 3P / Al-2.8wt.%Fe, (g) and (h) are Al2O 3P / Al-14wt.%Fe;

[0038] Figure 19 In this embodiment of the invention, in-situ Al2O2 prepared at different temperatures after being kept at a temperature of 1 hour was obtained. 3P A bar chart of wear amount of Al-Fe composite material;

[0039] Figures 20a to 20d SEM images of the wear sample surface directly placed in a furnace at 1200℃ and held for 1 hour in this embodiment of the invention: (a) shows Al2O 3P / Al-1.4wt.%Fe, (b) is Al2O 3P / Al-2.1wt.%Fe, (c) is Al2O 3P / Al-2.8wt.%Fe, (d) is Al2O 3P / Al-14wt.%Fe;

[0040] Figure 21 In this embodiment of the invention, Al2O is prepared by in-situ reaction at 1200℃ using a heating method. 3P / Al-Fe composite material wear effect histogram;

[0041] Figures 22a to 22d The SEM images of the wear sample surface in this embodiment of the invention are as follows: (a) shows Al2O3. The sample was heated to 1200℃ at a rate of 5℃ / min and held for 10 min. 3P / Al-1.4wt.%Fe, (b) is Al2O 3P / Al-2.1wt.%Fe, (c) is Al2O 3P / Al-2.8wt.%Fe, (d) is Al2O 3P / Al-14wt.%Fe. Detailed Implementation

[0042] 1. Experimental materials

[0043] The raw materials used in this embodiment are pure Al powder and nano-magnetic Fe2O3 powder; their particle size and purity are shown in Table 1:

[0044] Table 1 Raw materials used in the experiment

[0045]

[0046] 2Al2O 3P Preparation process of Al-Fe composite materials

[0047] Al2O 3P The preparation process of Al-Fe composite materials is as follows: Figure 1As shown: Al powder and Fe2O3 powder were weighed in a certain proportion, thoroughly mixed, and pressed into Al-Fe2O3 blocks using a universal testing machine. The blocks were then placed in a resistance furnace, and aluminum-based composite materials were prepared according to the process parameters shown in Table 2. The prepared aluminum-based composite materials were subjected to XRD analysis, microstructure observation, and tests for hardness and wear resistance.

[0048] 2.1 Preparation of compressed blocks

[0049] Using an electronic balance (accuracy 0.0001g), weigh Al powder and Fe2O3 powder according to the following proportions: (Al-2%Fe2O3, Al-3%Fe2O3, Al-4%Fe2O3, and Al-20%Fe2O3). Before mixing, dry the Fe2O3 powder at 180℃ for 2 hours, cool it to room temperature, and immediately mix it thoroughly with the Al powder for 30 minutes. Place the mixed (Al+Fe2O3) powder into a mold and press it using a universal testing machine. The cylindrical precast blocks are subjected to a pressure of 80kN and a holding time of 180s.

[0050] 2.2 Preparation of composite materials

[0051] Al-2wt.%Fe2O3, Al-3wt.%Fe2O3, Al-4wt.%Fe2O3, and Al-20wt.%Fe2O3 were grouped together and Al2O3 was prepared using the in-situ reaction process parameters shown in Table 2. 3P / Al-Fe composite material.

[0052] Table 2. Process parameters for in-situ reaction preparation of composite materials

[0053]

[0054]

[0055] 3. Effects of process parameters on Al2O 3P Influence of the microstructure of Al-Fe composite materials

[0056] When preparing composite materials through in-situ reaction, process parameters such as in-situ reaction temperature, holding time, and heating method will have a significant impact on the microstructure of the composite material.

[0057] 3.1 Phase composition and microstructure of the compressed briquettes

[0058] BSE (Back-Reflection Electron Detector) diagrams of Al-2wt.%Fe2O3, Al-3wt.%Fe2O3, Al-4wt.%Fe2O3, and Al-20wt.%Fe2O3 blocks are shown below. Figures 2a to 2dIn the image, bright Fe2O3 particles and their aggregates are distributed among the gray aluminum particles.

[0059] 3.2 Effect of heat preservation time on Al2O 3P Influence of the microstructure of Al-Fe composite materials

[0060] Two groups of Al-2wt%Fe2O3, Al-3wt%Fe2O3, Al-4wt%Fe2O3, and Al-20wt%Fe2O3 briquettes were directly placed into furnaces at 1100℃ and 1200℃ respectively, held for 10 min, and then cooled. The same two groups of Al-2wt%Fe2O3, Al-3wt%Fe2O3, Al-4wt%Fe2O3, and Al-20wt%Fe2O3 briquettes were then directly placed into furnaces at 1100℃ and 1200℃ respectively, held for 1 h, and then cooled. The effect of in-situ reaction temperature on the Al2O3 prepared by different holding times was investigated. 3P The influence of the microstructure of Al-Fe composite materials.

[0061] 3.2.1 Effect of in-situ reaction temperature on the microstructure of composite materials after 10 min of heat treatment

[0062] 3.2.1.1 Effect of in-situ reaction temperature on dispersed Al2O3 particles and their aggregates

[0063] Al2O 3P The low-magnification OM image of the Al-Fe composite material is shown below. Figures 3a to 3h As shown, the purpose is to observe the dispersibility of Al2O3 particles. In the figure, the gray phase is the Al matrix, the dark gray phase is the Al3Fe phase, and the black phase is the Al2O3 particles and their aggregates. It can be observed from the figure that some Al2O3 particles form particle aggregates, while some Al2O3 particles are dispersed. Overall, the Al2O3 particles and their aggregates are uniformly distributed in the Al matrix.

[0064] The microstructure of the composite material with a reaction temperature of 1100℃ is shown in the figure. Figure 3a , Figure 3c , Figure 3e and Figure 3g It can be observed that with the increase of Fe2O3 content, the number of Al2O3 particle agglomerates increases, and the size increases from <30μm to <150μm. The microstructure of the composite material at a reaction temperature of 1200℃ is shown in [Figure number missing]. Figure 3b , Figure 3d , Figure 3f and Figure 3hIt can be observed that with the increase of Fe2O3 content, the number of Al2O3 particle agglomerates increases, and the size increases from <50μm to <200μm. At different reaction temperatures, the Fe2O3 content has the same effect on the change in the size and number of Al2O3 particle agglomerates. With the increase of in-situ reaction temperature and Fe2O3 content, both the size and number of Al2O3 particle agglomerates increase.

[0065] High-magnification SEM images of the composite material are shown below. Figures 4a to 4h The purpose was to observe the particle size, morphology, and distribution of the dispersed Al2O3 particles. The microstructure of the composite material at a reaction temperature of 1100℃ is shown in [reference needed]. Figure 4a , Figure 4c , Figure 4e and Figure 4g The microstructure of the composite material with a reaction temperature of 1200℃ is shown in [reference needed]. Figure 4b , Figure 4d , Figure 4f and Figure 4h The in-situ reaction temperature and Fe2O3 content both affect the particle size, morphology, and distribution of dispersed Al2O3 particles. When the Fe2O3 content is <4%, the Al2O3 particles are larger. As the reaction temperature increases, the Al2O3 particles become more regular in morphology. With the increase of Fe2O3 content, the particle size of dispersed Al2O3 particles decreases slightly, and the morphology tends to be more regular. When the Fe2O3 content is 20%, the Al2O3 particles are rod-shaped, distributed along the original Al particle boundaries, and are smaller in size.

[0066] High-magnification SEM images of the composite material are shown below. Figures 5a to 5f The purpose was to observe the Al2O3 particle agglomerates. The microstructure of the composite material with an in-situ reaction temperature of 1100℃ is shown in [reference needed]. Figure 5a , Figure 5c and Figure 5e The microstructure of the composite material with an in-situ reaction temperature of 1200℃ is shown in [reference needed]. Figure 5b , Figure 5d and Figure 5f Observations show that the in-situ reaction temperature has little effect on Al2O3 particle agglomerates. The size of the Al2O3 particle agglomerates depends on the size of the Fe2O3 agglomerates in the compressed briquette. The larger the Fe2O3 particle agglomerates in the compressed briquette, the larger the Al2O3 particle agglomerates generated by the in-situ reaction. The size of the Al2O3 particle agglomerates has little effect on the particle size and number of large Al2O3 particles in the agglomerates, but it does affect the number of small Al2O3 particles.

[0067] 3.2.1.2 Effect of in-situ reaction temperature on the size and distribution of the Al3Fe phase in the composite material

[0068] BSE plots of composite materials at low magnification are shown below. Figures 6a to 6hThe purpose of this study is to observe the morphology, size, and distribution of the Al3Fe phase. In the figure, the bright areas represent the Al3Fe phase, the gray areas represent the Al matrix, and the black areas represent Al2O3 particles and their aggregates. The figure shows that the Al3Fe phase is uniformly distributed within the Al matrix. The microstructure of the composite material at a reaction temperature of 1100℃ is shown in the figure. Figure 6a , Figure 6c , Figure 6e and Figure 6g Al2O 3P / Al-1.4wt.%Fe,Al2O 3P / Al-2.1wt.%Fe and Al2O 3P In the Al-2.8wt.%Fe composite material, the Al3Fe phase fractures, mainly appearing as discontinuous needle-like or rod-like structures. Primary Al3Fe phases appear in the hypereutectic composition. The microstructure of the composite material at a reaction temperature of 1200℃ is shown below. Figure 6b , Figure 6d , Figure 6f and Figure 6h In Al2O 3P In the Al-1.4wt.%Fe composite material, the Al3Fe phase is mainly needle-like. With increasing Fe2O3 content, the Al3Fe phase fractures, gradually transforming from needle-like to discontinuous rod-like and then discontinuous blocky structures. 3P In the Al-14wt.%Fe composite material, the in-situ reaction temperature has little effect on the morphology of the Al3Fe phase, which is mainly in the form of irregular blocks. When the Fe2O3 content is the same, increasing the in-situ reaction temperature will improve the continuity of the Al3Fe phase.

[0069] High-magnification BSE plot of discontinuous Al3Fe phase in composite material is shown below. Figures 7a to 7d Discontinuous needle-like and discontinuous rod-like Al3Fe phases are observed. Figure 7a The discontinuity of the Al3Fe phase is due to the in-situ formation of Al2O3 particles within this phase. Discontinuous rod-shaped Al3Fe phases are shown below. Figure 7b It can be observed that the fracturing of the Al3Fe phase is caused not only by the influence of in-situ Al2O3 particles, but also by the boundaries of the incompletely fused original Al particles, which hinder the full diffusion of Fe. Discontinuous blocky Al3Fe phases are observed. Figure 7c and Figure 7d It can be observed that the fracture of the blocky Al3Fe phase is due to the formation of in-situ Al2O3 particles in the Al3Fe phase. When the Fe2O3 content increases, the number of in-situ Al2O3 particles increases, and the in-situ Al2O3 particles are mainly distributed along the boundaries of the original Al particles. Figure 7d Therefore, it has a stronger hindrance effect on the diffusion of Fe atoms, resulting in an increased degree of fracture of the bulk Al3Fe phase, and the fractured particles are nearly spherical.

[0070] 3.2.2 Effect of in-situ reaction temperature on the microstructure of composite materials after 1 hour of heat treatment

[0071] 3.2.2.1 Effect of in-situ reaction temperature on dispersed Al2O3 particles and their aggregates

[0072] Two groups of Al-2wt%Fe2O3, Al-3wt%Fe2O3, Al-4wt%Fe2O3, and Al-20wt%Fe2O3 briquettes were directly placed into furnaces at 1100℃ and 1200℃ respectively, held at that temperature for 1 hour, and then cooled in the furnace. The OM diagrams of the resulting composite materials are shown below. Figures 8a to 8h The microstructure of the composite material with an in-situ reaction temperature of 1100℃ is shown in [reference needed]. Figure 8a , Figure 8c , Figure 8e and Figure 8g It can be observed that with the increase of Fe2O3 content, the number of Al2O3 particle agglomerates increases, and the size increases from <50μm to <200μm. The microstructure of the composite material at a reaction temperature of 1200℃ is shown in [Figure number missing]. Figure 8b , Figure 8d , Figure 8f and Figure 8h It can be observed that with the increase of Fe2O3 content, the number of Al2O3 particle agglomerates increases, and the size increases from <80μm to <250μm. At different reaction temperatures, the Fe2O3 content has the same effect on the change in the size and number of Al2O3 particle agglomerates. With the increase of in-situ reaction temperature and Fe2O3 content, both the size and number of Al2O3 particle agglomerates increase.

[0073] Effect of heat preservation time: With the extension of heat preservation time, the size and number of Al2O3 particle agglomerates increase, and the size of Al3Fe phase increases.

[0074] Figure 9 shows a high-magnification SEM image of the composite material, the purpose of which is to observe the particle size, morphology, and distribution of the dispersed Al₂O₃ particles. The microstructure of the composite material at an in-situ reaction temperature of 1100℃ is shown in Figure 9. Figure 9a , Figure 9c , Figure 9e and Figure 9g As can be observed from the figure, in Figure 9a , Figure 9c and Figure 9e In the middle, Al2O3 particles have a relatively regular shape, nearly spherical, and in Figure 9g In the composite material, the Al2O3 particles are short rod-shaped and distributed along the boundaries of the original aluminum particles. The microstructure of the composite material with a reaction temperature of 1200℃ is shown in [reference needed]. Figure 9b , Figure 9d , Figure 9f and Figure 9h As can be observed from the figure, in Figure 9b , Figure 9d and Figure 9f In the figure, the dispersed Al2O3 particles are irregular in shape, and some Al2O3 particles can be seen to have aggregated and grown from smaller Al2O3 particles. Figure 9h In the composite material, the dispersed Al2O3 particles are short rod-shaped and distributed along the boundaries of the original Al particles. Compared with the Al2O3 particles in the composite material after 10 min of heat preservation, the Al2O3 particles in the composite material after 1 h of heat preservation have a larger particle size.

[0075] The above analysis shows that both the in-situ reaction temperature and the Fe2O3 content affect the particle size, morphology, and distribution of dispersed Al2O3 particles. With increasing Fe2O3 content, the particle size of dispersed Al2O3 decreases, and the morphology becomes more regular. With increasing reaction temperature, the dispersed Al2O3 particles become larger.

[0076] 3.2.2.2 Effect of heat preservation time on the size and distribution of Al3Fe particles in the composite material

[0077] BSE plots of composite materials at low magnification are shown below. Figures 10a to 10h The purpose was to observe the morphology, size, and distribution of the Al3Fe phase. The figures show that the Al3Fe phase is uniformly distributed within the Al matrix, similar to the Al3Fe phase in the composite material prepared by holding at 10 min. The fractured Al3Fe phase forms discontinuous needle-like, rod-like, and blocky Al3Fe structures. The microstructure of the composite material with an in-situ reaction temperature of 1100℃ is shown in the figure. Figure 10a , Figure 10c , Figure 10e and Figure 10g As can be observed from the figure, in Figure 10a , Figure 10c and Figure 10e In the composite material, the Al3Fe phase is mainly in the form of discontinuous rod-like and discontinuous needle-like structures, which is different from the Al3Fe phase in the composite material after 10 min of heat treatment. Figure 9a , Figure 9c and Figure 9e In the composite material after 1 hour of heat preservation, the number of rod-shaped Al3Fe increased and the degree of fracture increased. Figure 10e The primary Al3Fe phase appears, and its degree of fracture is also greater. Figure 10g In the composite material, the Al3Fe phase mainly exists as irregular and discontinuous blocks. The microstructure of the composite material with an in-situ reaction temperature of 1200℃ is shown in [reference needed]. Figure 10b , Figure 10d , Figure 10f and Figure 10h As can be observed from the figure, in Figure 10b In the middle, the Al3Fe phase is mainly needle-like, and there is also a granular Al3Fe phase. Figure 10b , Figure 10dIn the sample, the Al3Fe phase is mainly rod-shaped, with discontinuous needle-shaped and granular Al3Fe phases present, and primary Al3Fe phases are also observed. Figure 10f Compared to Al3Fe Figure 9d The Al3Fe in the middle layer is large in size; Figure 10h The Al3Fe phase is mainly in the form of irregular, discontinuous blocks.

[0078] Through the Figure 10a and Figure 10b , Figure 10c and Figure 10d , Figure 10e and Figure 10f , Figure 10g and Figure 10h Comparative observation shows that when the Fe2O3 content is the same, the higher the in-situ reaction temperature, the finer the rod-shaped Al3Fe phase becomes, and the less the blocky Al3Fe phase breaks.

[0079] 3.3 Heating methods for Al2O 3P Influence of the microstructure of Al-Fe composite materials

[0080] In-situ reactions between Al and Fe2O3 require heating to occur. Different heating methods affect the reaction rate, thus influencing the reaction process and ultimately the in-situ Al2O3 reaction. 3P The properties of Al-Fe composite materials. When Al-Fe2O3 briquettes are heated in the furnace, the in-situ reaction starts at a low temperature and the reaction rate is relatively slow. However, when the furnace is heated to a set temperature and the Al-Fe2O3 briquettes are placed directly into the furnace, the in-situ reaction starts at a high temperature and the reaction rate is relatively fast. A group of Al-2wt%Fe2O3, Al-3wt%Fe2O3, Al-4wt%Fe2O3, and Al-20wt%Fe2O3 briquettes were heated in the furnace at a rate of 5℃ / min to 1200℃, held for 10 min, and then cooled in the furnace. The microstructure was compared with that of a previously analyzed group of composite materials (Al-2wt%Fe2O3, Al-3wt%Fe2O3, Al-4wt%Fe2O3, and Al-20wt%Fe2O3 briquettes were placed directly into a 1200℃ furnace, held for 10 min, and then cooled in the furnace) to investigate the effect of the heating method on the microstructure of the composite materials.

[0081] 3.3.1 Effect of heating method on particle size and distribution of Al2O3 particles and their aggregates in composite materials

[0082] Al2O 3P The low-magnification OM image of the Al-Fe composite material is shown below. Figures 11a to 11h The purpose was to observe the distribution of Al2O3 particles and their aggregates. The microstructure of the composite material prepared by furnace heating at 5℃ / min is shown in [Figure / Image]. Figure 11a , Figure 11c , Figure 11e and Figure 11g As can be observed from the figure, in Figure 11a , Figure 11c and Figure 11e In the middle, the number and size of Al2O3 particle agglomerates are not significantly different, both being approximately <30 μm. Figure 11g The Al2O3 particle agglomerates are <150 μm. The microstructure of the composite material directly placed in a 1200℃ furnace is shown in [reference needed]. Figure 11b , Figure 11d , Figure 11f and Figure 11h From "3.2.2.1" Figures 8a to 8h Analysis shows that as the Fe2O3 content increases, the size of Al2O3 particle agglomerates increases from <50μm to <200μm.

[0083] The heating method and Fe2O3 content both affect the number and size of Al2O3 particle agglomerates. As the Fe2O3 content increases, both the number and size of Al2O3 particle agglomerates increase. In composite materials directly placed in a furnace at 1200℃, the number and size of Al2O3 particle agglomerates are relatively large.

[0084] High-magnification SEM images of the composite material are shown below. Figures 12a to 12h The purpose was to observe the particle size, morphology, and distribution of the dispersed Al2O3 particles. The microstructure of the composite material prepared by furnace heating at 5℃ / min is shown in [Figure number missing]. Figure 12a , Figure 12c , Figure 12e and Figure 12g As the percentage of Fe2O3 increases, the particle size of Al2O3 decreases. Figure 12g In the composite material, the Al2O3 particles are short rod-shaped with a particle size of <6μm, distributed along the boundaries of the original aluminum particles. The percentage of the composite material directly added to the furnace has little effect on the morphology and size of the Al2O3 particles. Figure 12h In the original sample, the Al2O3 particles were short rod-shaped with a particle size of <10μm; the Al2O3 particles in the composite material prepared by directly placing them into the furnace were relatively small.

[0085] 3.3.2 Effect of heating method on the size and distribution of Al3Fe phase in composite materials

[0086] The BSE plot of the composite material at low magnification is shown below. Figures 13a to 13h The purpose was to observe the morphology, size, and distribution of the Al3Fe phase. The microstructure of the composite material prepared by furnace heating at 5℃ / min is shown in [Figure number missing]. Figure 13a , Figure 13c , Figure 13e and Figure 13g Granular Al3Fe can be observed in the figures. Figure 13a The Al3Fe phase mainly occurs in needle-like forms, with a small amount appearing as discontinuous rod-like structures. Figure 13c The Al3Fe phase mainly occurs in needle-like forms, with a small amount appearing as discontinuous rod-like shapes. Primary Al3Fe phase crystals are present. Figure 13e In the primary Al3Fe phase, the Al3Fe phase is mainly rod-shaped, with a small amount appearing as needles. The size of the primary Al3Fe phase increases. Figure 13c and Figure 13e In the process, in-situ Al2O3 particles are distributed within the primary Al3Fe phase, but this does not cause the primary Al3Fe phase to fracture. Figure 13g In the composite material, the Al3Fe phase mainly exists as irregular, discontinuous blocks, with a small amount existing as discontinuous needles. The morphology of the discontinuous blocky structure is similar to that of the aluminum matrix in the briquettes. The microstructure of the composite material directly placed in the furnace is shown in [reference needed]. Figure 13b , Figure 13d , Figure 13f and Figure 13h As the Fe2O3 content increases, the morphology of the Al3Fe phase changes from needle-like to discontinuous rod-like and discontinuous coarse block-like.

[0087] The above analysis shows that both the heating method and the Fe2O3 content affect the Al3Fe phase. 3P The morphology and distribution of granular, needle-like, discontinuous needle-like, and discontinuous rod-like Al3Fe phases in Al-Fe composites have little impact, but the morphology of bulk Al3Fe phases is significantly affected. In composites prepared by directly placing the bulk Al3Fe phase into the furnace, the degree of fracture of the bulk Al3Fe phase is higher. With the increase of Fe2O3 content, primary Al3Fe phase appears in the eutectic composition.

[0088] 4Al2O 3P Evaluation of the hardness and wear resistance of Al-Fe composite materials

[0089] Al2O 3P The mechanical properties of Al-Fe composites are mainly affected by the combined action of Al2O3 ceramic phase particles and Al3Fe intermetallic compounds, while the strengthening is related to the morphology, size, quantity and distribution of Al2O3 particles and Al3Fe.

[0090] 4.1 Hardness

[0091] The bar charts showing the hardness of the composite materials prepared at different in-situ reaction temperatures and after holding at the temperature for 10 min are shown below. Figure 14 As can be observed from the figure, the hardness of both composite materials increases with increasing Fe content. Figure 14 The black color indicates the hardness of the composite material with an in-situ reaction temperature of 1100℃, and its hardness value increases from 26.7HV to 40.6HV. Figure 14The red area represents the hardness of the composite material prepared at an in-situ reaction temperature of 1200℃, where the hardness value increases from 37.4 HV to 46.7 HV. The hardness value at 1200℃ is generally higher than that at 1100℃. Experimental results show that the composite material prepared with an Fe2O3 content of 20wt%, an in-situ reaction temperature of 1200℃, and a holding time of 10 min exhibits good hardness.

[0092] The bar charts showing the hardness of the composite materials prepared at different in-situ reaction temperatures and after 1 hour of incubation are shown below. Figure 15 As can be observed from the figure, the hardness of both composite materials increases with the increase of Fe2O3 content. Figure 15 The black color indicates the hardness of the composite material with an in-situ reaction temperature of 1100℃, and its hardness value increases from 28.5HV to 41.5HV. Figure 15 The red area represents the hardness of the composite material prepared at an in-situ reaction temperature of 1200℃, where the hardness value increases from 40.6 HV to 49.8 HV. The hardness value at 1200℃ is generally higher than that at 1100℃. Compared to the composite material prepared at 10 min, the change pattern is similar, but the hardness of the composite material prepared at 1 h is generally higher than that prepared at 10 min. The experimental results show that the composite material prepared with an Fe2O3 content of 20 wt%, an in-situ reaction temperature of 1200℃, and a 1 h holding time exhibits good wear resistance.

[0093] The bar charts showing the hardness of composite materials prepared by heating to 1200℃ and holding for 10 min using different heating methods are shown below. Figure 16 As can be observed from the figure, the hardness of both composite materials increases with increasing Fe content. Figure 16 The medium black color indicates the hardness of the composite material when the furnace temperature is increased at 5℃ / min, with the hardness value increasing from 40.6HV to 52.1HV; Figure 16 The red area represents the hardness of the composite material directly placed in a 1200℃ furnace, with the hardness value increasing from 37.4 HV to 46.7 HV. It can be observed that the hardness of the composite material heated at 5℃ / min with the furnace is generally higher than that of the composite material directly placed in the 1200℃ furnace. The experimental results show that, with an Fe2O3 content of 20wt.%, the composite material prepared by heating at 5℃ / min with the furnace exhibits better hardness.

[0094] The above analysis shows that the composite material prepared with an Fe2O3 content of 20 wt.% and a furnace temperature of 5℃ / min to 1200℃ and a holding time of 10 min has the best hardness.

[0095] 4.2 Abrasion resistance

[0096] For Al2O 3PFor Al-Fe2O3 composite materials, their wear resistance is mainly affected by the morphology (content, shape, size, and distribution of Al2O3 particles and Al3Fe phase), rotational speed, time, and applied load. Among these factors, the content of Al2O3 and Al3Fe phases and the applied load play a major role in the wear resistance of the composite material. Therefore, this embodiment studies the effects of different Fe2O3 contents, holding time, and heating methods on the wear resistance of Al2O3 composite materials by measuring the wear amount. 3P The influence of Al-Fe2O3 composite material on wear resistance and wear morphology.

[0097] The wear resistance of the composite material is visually illustrated by measuring the wear loss weight. The wear amount of the composite material prepared at different in-situ reaction temperatures and after holding for 10 minutes is shown in the bar chart. Figure 17 As can be observed from the figure, the hardness and wear of both composite materials decrease with increasing Fe content. Figure 17 The black color represents the wear amount of the composite material with an in-situ reaction temperature of 1100℃, which decreased from 19.6mg to 14.5mg. Figure 17 The red area represents the wear amount of the composite material with an in-situ reaction temperature of 1200℃, which decreased from 15.4 mg to 10.7 mg. The wear amount at 1200℃ is generally lower than that at 1100℃. The experimental results show that the composite material prepared with an Fe2O3 content of 20wt%, an in-situ reaction temperature of 1200℃, and a holding time of 10 min exhibits good wear resistance.

[0098] By observing the wear surface morphology of the composite material after friction and wear tests, the friction and wear mechanism of the composite material can be determined. SEM was used to observe Al2O... 3P The wear morphology of Al-Fe composite materials is shown in [reference]. Figures 18a to 18h .

[0099] Figures 18a to 18hThe surface consists of furrows and pits formed by the shedding of hard phases. The friction and wear mechanism of the composite material is abrasive wear. With increasing Fe2O3 content, more Al2O3 and Al3Fe are generated, increasing the hardness of the composite material. This increased hardness improves the wear resistance of the composite material. During wear, the softer aluminum matrix is ​​worn first, while the harder Al2O3 particles and Al3Fe phase protrude from the friction test surface. Thus, the main load applied to the sample is concentrated on the wear-resistant Al2O3 particles and Al3Fe phase. The presence of Al2O3 particles and Al3Fe phase significantly reduces matrix wear during the wear process; the hard Al2O3 particles act as a "protector of the aluminum matrix." Furthermore, the in-situ preparation method effectively improves the interfacial bonding strength of the composite material, thereby reducing the number of Al2O3 particles detached from the matrix and significantly improving the wear resistance of the composite material. The furrow depth on the worn surface gradually decreases, and the amount of abrasive detachment decreases. Furthermore, the wear analysis based on the above measurements shows that the wear gradually decreases with increasing Fe2O3 content, thus improving the material's service life. Since the wear mechanism of the composite material is the same under other in-situ reaction process parameters, it will not be discussed further.

[0100] The wear amount of the composite materials prepared at different in-situ reaction temperatures and after 1 hour of heat treatment is shown in the bar chart. Figure 19 As can be observed from the figure, the hardness and wear of both composite materials decrease with increasing Fe content. Figure 19 The black color represents the wear amount of the composite material with an in-situ reaction temperature of 1100℃, which decreased from 18.9mg to 13.8mg. Figure 19 The red area represents the wear amount of the composite material with an in-situ reaction temperature of 1200℃, which decreased from 14.1 mg to 9.3 mg. The wear amount at 1200℃ is generally lower than that at 1100℃. The experimental results show that the composite material prepared with an Fe2O3 content of 20 wt.% and an in-situ reaction temperature of 1200℃ for 1 hour exhibits good wear resistance.

[0101] Figures 20a to 20d The surface consists of furrows and pits formed by the shedding of hard phases. As the Fe2O3 content increases, the boundaries of the furrows on the worn surface become smoother.

[0102] The wear amount of the composite materials prepared by heating to 1200℃ and holding for 10 min using different heating methods is shown in the bar chart. Figure 21 As can be observed from the figure, the wear of both composite materials decreases with increasing Fe content. Figure 21 The black color indicates the wear amount of the composite material when the furnace temperature is increased at 5℃ / min, and the wear amount decreases from 13.9mg to 8.7mg. Figure 21The red area represents the wear amount of the composite material directly placed in a 1200℃ furnace, which decreased from 15.4 mg to 10.7 mg. It can be observed that the wear amount of the composite material heated at 5℃ / min with the furnace is generally higher than that of the composite material directly placed in the 1200℃ furnace. The experimental results show that the composite material prepared with a Fe2O3 content of 20wt.% and a furnace heating method of 5℃ / min exhibits good wear resistance.

[0103] Figures 22a to 22d The surface consists of furrows and pits formed by the shedding of hard phase. With increasing Fe2O3 content, the furrow boundaries on the worn surface become smoother. The above analysis indicates that the composite material prepared with an Fe2O3 content of 20 wt.%, heated to 1200℃ at a furnace temperature of 5℃ / min and held for 10 min, exhibits the best wear resistance.

[0104] 5. Conclusion

[0105] In this embodiment, Al-2wt.%Fe₂O₃, Al-3wt.%Fe₂O₃, Al-4wt.%Fe₂O₃, and Al-20wt.%Fe₂O₃ systems were selected, and Al₂O₃ was prepared by in-situ reaction method. 3P / Al-1.4wt.%Fe,Al2O 3P / Al-2.1wt.%Fe、Al2O 3P / Al-2.8wt.%Fe and Al2O 3P The effects of in-situ reaction temperature, holding time, and heating method on the dispersibility, particle size, morphology, and distribution of in-situ Al2O3 particles in the composite material, as well as their effects on the morphology, size, and distribution of the Al3Fe phase, were investigated. The influence of process parameters on Al2O3 was also studied. 3P The influence of Al-Fe composite materials on hardness and wear resistance was investigated, and the following conclusions were drawn:

[0106] 1. The composite material forms dispersed Al2O3 particles and Al2O3 particle agglomerates. The dispersed irregularly shaped and nearly spherical Al2O3 particles are mainly distributed in the Al matrix and Al3Fe phase. The dispersed rod-shaped Al2O3 particles are mainly distributed along the boundaries of the original Al particles. Large-sized Al2O3 particles are formed by the aggregation of smaller Al2O3 particles. Due to the interaction between the Al2O3 particles and the original Al boundary, the Al3Fe phase is fractured, mainly in the form of discontinuous needle-shaped, rod-shaped and block-shaped phases. A small amount of granular and needle-shaped Al3Fe phases are present in all composite materials.

[0107] 2. When the composite material is directly placed in a furnace at 1100℃ after holding at a temperature for 10 minutes, as the Fe2O3 content increases, the Al2O3 particle agglomerates increase from <30μm to <150μm; the Al2O3 particles decrease from <9μm to <8μm, and change from irregular blocks to short rods; the Al3Fe phase changes from discontinuous needle-like → discontinuous rod-like → discontinuous blocky.

[0108] 3. When the composite material is directly placed in a furnace at 1200℃ after holding at a temperature for 10 minutes, as the Fe2O3 content increases, the Al2O3 particle agglomerates increase from <50μm to <200μm; the Al2O3 particles decrease from <10μm to <8μm, and change from regular blocky to short rod-shaped; the Al3Fe phase changes from needle-shaped to irregular rod-shaped to irregular blocky.

[0109] 4. When the composite material is directly placed in a furnace at 1100℃ after being kept at a constant temperature for 1 hour, as the Fe2O3 content increases, the Al2O3 particle agglomerates increase from <50μm to <200μm; the Al2O3 particles increase from <8μm to <10μm, and change from near-spherical to short rod-shaped; the Al3Fe phase changes from discontinuous needle-shaped to discontinuous rod-shaped to discontinuous block-shaped.

[0110] 5. When the composite material is directly placed in a furnace at 1200℃ after being kept at a constant temperature for 1 hour, as the Fe2O3 content increases, the Al2O3 particle agglomerates increase from <80μm to <250μm; the Al2O3 particles decrease from <10μm to <8μm, and change from near-spherical to short rod-shaped; the Al3Fe phase changes from needle-like to discontinuous needle-like + rod-like to discontinuous blocky.

[0111] 6. The composite material prepared by heating the furnace to 1200℃ at a rate of 5℃ / min showed that, with the increase of Fe2O3 content, the Al2O3 particle agglomerates increased from <50μm to <200μm; the Al2O3 particles decreased from <10μm to <8μm, and changed from near-spherical to short rod-shaped; the Al3Fe phase changed from needle-like to discontinuous rod-like to discontinuous blocky.

[0112] 7. With the increase of Fe2O3 content, in-situ reaction temperature, and holding time, the aspect ratio of Al3Fe phase decreases while its quantity increases, leading to increased hardness and wear resistance of the composite material. However, the heating method has the greatest impact on the composite material's properties. Al2O3 prepared by furnace heating to 1200℃ at 5℃ / min and holding for 10min... 3P The Al-14wt.%Fe composite material has the highest hardness at 49.8HV and the lowest wear at 9.3mg.

Claims

1. An Al2O 3P The method for preparing Al-Fe composite materials is characterized by, Includes the following steps: Step (1): After drying the nano-magnetic iron oxide powder and cooling it to room temperature, immediately mix it thoroughly with aluminum powder to obtain a mixed raw material powder; the particle size of the nano-magnetic iron oxide powder is 5-40 nm, and the mass fraction of nano-magnetic iron oxide powder in the mixed raw material powder is 2-20 wt.%. Step (2): Press the mixed raw material powder into a cylindrical preform. Step (3): Place the cylindrical preform into a resistance furnace for sintering. After sintering, Al2O3 is obtained. 3P / Al-Fe composite material; During sintering, the heating method is either heating with the furnace or placing the preform into the furnace at the set temperature. When placing the preform into the furnace at the set temperature, first raise the temperature of the resistance furnace to 1100-1200℃, then place the cylindrical preform into the resistance furnace and hold it at that temperature for 10 minutes or 1 hour. When heating with the furnace, place the cylindrical preform into the resistance furnace and raise the temperature to 1200℃ at a rate of 5℃ / min, then hold it at that temperature for 10 minutes or 1 hour. The composite material contains alumina particles and an Al3Fe phase; the alumina particles exist in the form of alumina particle aggregates, rod-shaped, near-spherical, and irregular shapes, or a mixture of two or more of these; the Al3Fe phase exists in the form of discontinuous granular, needle-shaped, rod-shaped, or blocky shapes, or a mixture of two or more of these.

2. The Al2O as described in claim 1 3P The method for preparing Al-Fe composite materials is characterized by, In step (1), the aluminum powder has a particle size of 30-80 μm and a purity greater than or equal to 99.0 wt.%; the nano magnetic iron oxide powder has a purity greater than or equal to 98.0 wt.%.

3. The Al2O as described in claim 1 3P The method for preparing Al-Fe composite materials is characterized by, In step (1), the drying temperature of the nano magnetic iron oxide powder is 150-300℃ and the drying time is 1.5-2.5h; the mixing time with aluminum powder after drying is 20-35min.

4. The Al2O as described in claim 3 3P The method for preparing Al-Fe composite materials is characterized by, In step (1), the drying temperature of the nano magnetic iron oxide powder is 180℃ and the drying time is 2h; the mixing time with aluminum powder after drying is 30min.

5. The Al2O according to claim 1 3P The method for preparing Al-Fe composite materials is characterized by, In step (2), the material is pressed at room temperature with a pressure of 75-85 kN and a holding time of 160-200 s.

6. The Al2O according to claim 5 3P The method for preparing Al-Fe composite materials is characterized by, In step (2), the pressure is 80kN and the holding time is 180s during the pressing process; the size of the cylindrical precast block is ∅20×10mm.

Citation Information

Patent Citations

  • Method for preparing Fe3Al-Al2O3 composite material

    CN102021473A

  • High-temperature-resistant aluminum alloy composite material and preparation method thereof

    CN112853163A